Soil characterisation for teak (Tectona grandis) plantations in the Nzara district of Southern Sudan - Ombina, Christian Ahmed (Stellenbosch : Stellenbosch University, 2008)
Thesis (MScFor (Forest and Wood Science))--Stellenbosch University, 2008.